EXPLORING CRITICAL LITERACY IN INDONESIAN LANGUAGE LEARNING AT THE JUNIOR HIGH SCHOOL - Nurhidayah Nurhidayah; Esti Swatika Sari; Beniati Lestyarini (Program Studi PGSD Universitas Flores, 2026)
The increasing ease of access to information has the potential to introduce new challenges in selecting accurate information. Therefore, students need to be equipped with critical literacy skills to obtain accurate and reliable information. This study focuses on how critical literacy is introduced, trained, and/or practiced in the school environment, particularly in Indonesian language learning. This research is a narrative inquiry that describes all research experiences, including initial observations, research planning, and research results, in narrative form with more flexible sentence structures. The research was conducted in the Special Region of Yogyakarta. The data used in this research are qualitative and were collected through interviews, document analysis, and observation. Focus Group Discussions were conducted with literacy and language learning experts and junior high school Indonesian language teachers. The research findings indicate that Indonesian language-teaching practices have begun to incorporate literacy skills but have not yet reached an optimal critical stage. Teaching involves understanding discourse, vocabulary, sentences, and texts; understanding explicit and implicit information in texts or intertexts; drawing conclusions and making connections between texts or intertexts; and conveying information from texts in other forms.